Proposition des activités de correction phonétique des voyelles nasales chez les étudiants serbophones de FLE à la Faculté de Philosophie et Lettres de Novi Sad – vers une approche éclectique - Lazarević, Ana (Verbum – Analecta Neolatina, 2024)
The purpose of this paper is to complete existing phonological correction exercises for French nasal vowels for students speaking Serbian as L1, who attended the Faculty of Philosophy in Novi Sad in 2019–2020. Our approach is eclectic, and the exercises are based on a system of mistakes that was developed by examining how participants produced these vowels in prior study (Lazarević, 2023). Oral production activities in context are given particular focus because they do not appear to be covered in detail in workbooks on FSL phonetics. Our goal is to examine current nasal vowel pronunciation teaching strategies and contrast them with the ones we will present. The evaluation of our phonetic correction exercises confirmed that the production improves more easily when it comes to isolated words and phrases, while mistakes frequently recur during semi-spontaneous oral output.